The impact of addition of xanthan gum and guar gum on rheological properties of foams produced by continuous method - Kabziński, Maciej; Neupauer, Krzysztof; Nowak, Marcelina; Kruk, Joanna; Kaczmarczyk, Kacper (Polimery, 2021)
The paper presents the effect of the addition of hydrocolloids – xanthan gum and guar gum – on the rheological properties of ovoalbumin-based food foams, produced by continuous method. The foaming was carried out in a column apparatus with additional aeration equipped with a paddle stirrer. In order to determine the rheological parameters, a hysteresis loop test was carried out. The results of the study were described using the Ostwald-de Waele equation. The effect of the addition of hydrocolloid on the rheological properties of the obtained foams was characterized, and the synergistic effects between the hydrocolloids used were described.